Konsumsi Parfum Mewah oleh Konsumen Indonesia dalam Perspektif Masstige Brand - Hambalah, Febrina (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2023)
The use of perfume for Indonesian consumers not only serves to fulfill the user's need for a pleasant aroma, but also shows prestige for the perfume user. Consumers with middle incomes also want to experience this luxury value through Masstige brand perfume. This research aims to explain how purchasing masstige brand perfume is a starting point for consumers to experience the luxury value presented by luxury brands. This research method is through literature study. The data in this research was obtained from the collection of various literature sources relevant to this research topic. The results of this research are that Indonesian consumers consume Masstige brand perfume because they pursue symbolic value, experiential value and functional value. These three values ​​are components contained in the luxury value of a brand.